Development of specific tests for rapid detection of Escherichia coli and all species of Proteus in urine. - Hayward, N J (1977)
Proteus mirabilis was distinguishable from Escherichia coli and from several other species that may be associated with urinary tract infections when grown in a nutrient medium supplemented with 0.1 M L-methionine by the formation of large amounts of dimethyl disulfide and methyl mercaptan, which were detected by head-space gas-liquid chromatography (HS-GLC). E. coli could be detected by the same HS-GLC technique by ethanol production from methionine peptone water enriched with 1% either lactose or arabinose but not by any product from 10 amino acids tested. Ethanol from lactose was detected early in the exponential phase of growth. Significant numbers, 10(5) or more per ml, of E. coli in urine could be detected in about 5 h by ethanol production from an unshaken culture of urine in lactose methionine peptone water buffered at pH 7.2 (urine test medium); only a trace of dimethyl disulfide was produced. Significant numbers of P. mirabilis in urine could be detected in 4 h by dimethyl disulfide production and in 5 h by methyl mercaptan production from a shaken culture of urine in urine test medium; no ethanol was produced. Incubation of urine specimens in the test medium followed by examination by HS-GLC is proposed as a rapid method of detecting whether or not the urine contains significant numbers of E. coli or a species of Proteus.